Gestão do conhecimento e redes interorganizacionais em organizações públicas de turismo - Cacho, Andréa do Nascimento Barbosa (2019)
Tourism is a multifaceted sector based on knowledge and cooperation, mainly, because its complexity conditions. Knowledge management (KM) and interorganizational networks (IN) can facilitate the following KM process: acquisition, use, sharing, learning and cooperation between Public Tourism Organizations (PTO’s). Based on that, this proposal aim is to understand how knowledge management and interorganization network can help tourism public organization in the development of a tourism destination under the perception of experts in a city in the Northeast of Brazil. It’s a qualitative and exploratory research which study a newly fact: KM and IN in PTO’s. It has adopted an interpretative approach because it has the will to a deep comprehension about the studies subjects. The interviewees were chosen based on the proximity to the research problem. In total, it has been elected 17 (seventeen) interviewees from a non-probabilistic and intentional sample and snowball sampling procedure was applied whereby the first participants were asked to suggest other people who might be worth contacting to plan an interview. The data collection was obtained from bibliography research to find research gaps, through search conducted from 2016 to 2018 using The Brazilian Journal Portal to select the papers, while primary search was collected through semi structure interview guide. Among the techniques utilized in order to treat and analyze data are triangulation, documentary and content analysis. It has been used a qualitative software, entitle NVivo to facilitate data organization, word frequency and word cloud. The results found that most of the interviewees are experts with more than 30 years of experience with large know how in tourism planning and working on management and leadership areas. It has been found that PTO’s do not adopt KM as a systematic activity, in fact it has been identified some KM isolated actions. In the case of knowledge acquisition, it has been observed that PTO’s collect information from the main partner always when is required. It has been verified that knowledge sharing process of information occurs from partnership between stakeholders, through organization’s meeting. In addition, the interviewees have mentioned that social media (Facebook, Instagram and WhatsApp) is been used as a facilitator of sharing information, as much internal than external. However, it has been observed that through direct observation the medias are truly working as publicize media. So, they make public everything they are doing at PTO’s. It has been identified that PTO’s are not learning organization, but from the interviewees point of view it has been identified some attitudes in order to enhance the organization performance. In the case of KM evaluation, it has been identified that there is an effort to review old practice. For instance, one of PTO’s has been conducted an organization study to review the organization structure. As a general result, it has been proposed a theoretical framework which includes these main categories: acquisition, use, sharing, learning, evaluation, disposal and partnership.